Integrated nutrient management in lemon (Citrus limon Burm) cv. pant lemon-1 (Indian Journal of Arid Horticulture, 2025)
Citrus occupies an important position in fruit industy on account of its great utility. In Tarai, lemon has been found to be the most successful fruit due to its adapt- ability and availability of fruits throughout the year. among several cultivars grown, Pant Lemaon-1 is the most prom- ising in Tarai condition of Uttarakhand.it is a singal plant selection from "Kagzi kalan Lemon" (Baldevraj, 1990). It bears flowers and fruits in two main flushes and exhausts more nutrients to maintain vegetative growth which can support flowering and fruiting. To meet the requirement of nutrients recommended for different fruit crops, it could be either is supplied through inorganic source, but each one has its limitations. For meeting nutrient requirement, a re- cent emphasis has been given on the integrated nutrient management (INM). Integrated nutrient management is the combined use of organic and inorganic fertilizers and relies on use of FYM, crop residuse, legumes, biofertilizers, biopestisides. Looking into the importance of nutrient management, the present expriment "Integrated nutrient management in lemon cv.
Keywords: residuse; legumes; biofertilizers; biopestisides; Citrus occupies